(untitled) (Conference Zone, 2022)
Today, students learn the secrets of military education and lessons, traditions, national and spiritual values collected by ancestors and taking his rightful place in society based on life experience, knowledge potential and in the formation of his worldview, a teacher of military education up to the draft, his formation of professional competence is important. That is why it is important to increase attention to this field. The article talks about improving the lexical competence of military students in the Russian language classes.